Loop-mediated isothermal amplification coupled with a nanoparticle-based lateral biosensor for rapid, sensitive, and specific detection of Talaromyces marneffei - Zhou, Yuhong; Ye, Rui; Wang, Yizhe; Zhao, Xue; Yu, Honglan; Wang, Yu (Frontiers in Microbiology, 2025)
IntroductionTalaromyces marneffei (T.marneffei) is a pathogenic dimorphic fungus endemic in Southeast Asia and southern China. It can be found in the environment (soil and decaying wood) and may infect human hosts following the inhalation of spores. The disseminated infection of T.marneffei can be life-threatening without timely diagnosis and effective antifungal therapy.MethodsHerein, we proposed a simple, rapid, sensitive and visual point-of-care detection method for detecting T.marneffei using loop-mediated isothermal amplification combined with a nanoparticle-based lateral flow biosensor (T.marneffei-LAMP-LFB). A set of six primers was designed based on the internal transcribed spacer (ITS) region of the rRNA gene of T.marneffei.ResultsThe results of the T.marneffei-LAMP were visually reported by the biosensor within 2 min. A range of pathogenic organisms, including various fungus species, as well as several Gram-negative and Gram-positive bacterial species and viruses, were used to determine the analytical sensitivity and specificity of the assay. The optimal reaction condition for the T.marneffei-LAMP-LFB assay was 67 °C within 40 min. The T.marneffei-LAMP-LFB was able to detect up to 400 ag per test. No cross-reactions to non-T.marneffei strains were obtained. The entire procedure, including sample processing (15 min), LAMP reaction (40 min), and result reporting (within 2 min), could be completed within 60 min. Among 120 whole blood samples tested, 25 (20.83%) were T.marneffei-positive by T.marneffei-LAMP-LFB, with a diagnostic accuracy of 100% when compared to fungal culture assay.ConclusionThe T.marneffei-LAMP-LFB assay targeting the ITS region of the rRNA gene is a rapid, highly sensitive, specific, and straightforward diagnostic tool that may be suitable for use in point-of-care settings and basic medical facilities, especially in rural areas.